Decoupled responses of leaf and root decomposition to nutrient deposition in a subtropical plantation. (May 2022) - Wang, Yuxin; Wang, Huimin; Dai, Xiaoqin; Kou, Liang; Meng, Shengwang; Fu, Xiaoli
Abstract: The decomposition of leaf and root litter plays an important role in the cycling of nutrients and carbon (C) in ecosystems. The long-term patterns of mass loss during leaf and root decomposition are well documented, but the long-term responses of mass loss and C quality during the decomposition of these two types of litter to the simultaneous deposition of exogenous nitrogen (N) and phosphorus (P) are not known. We compared the responses of the rate of mass loss, C quality, and the enzymatic and chemical properties of root and leaf litters in the early and late phases of decomposition to N and P addition in a subtropical plantation. N and P addition had delayed effects on root decomposition compared with leaf decomposition. The addition of N and P promoted leaf decomposition in the early phase likely by alleviating the P limitation of microorganisms, indicated by the higher P concentration and lower N/P ratio. The addition of N and P, however, stimulated the decomposition of root litter in the late phase, which was associated with increases in the concentrations of manganese and P in the root residues. The addition of N and P decreased the C quality of the leaf residue in the late phase but had little effect on the C quality of the root residue, even though N and P addition decreased the activity of acid phosphatase and increased the ratio of activities of β-glucosidase to acid phosphatase in the root residue. The decoupled responses of mass loss and C quality during leaf and root decomposition to N and P addition highlight the need to distinguish between leaf and root litter in the late phase of decomposition when evaluating the impact of atmospheric N and P deposition on the cycling of C and nutrients. Highlights: Root decomposition responded to NP addition slower than leaf decomposition. NP addition promoted leaf decomposition in early phase of decomposition. NP addition promoted root decomposition in late phase of decomposition. NP addition decreased carbon quality of leaves but not roots in late phase. NP addition decreased activity of acid phosphatase in roots in late phase.